The land snails of Sungai Rawog Conservation Area, Telupid, Sabah, Malaysia - Liew, Thor Seng; Chang, Z.Y. (2019)
This paper presents the first checklist of land snails of Sungai Rawog Conservation Area (SRCA). The specimens of land snails were collected from 12 standard sampling plots and several random locations in the SRCA between 9th and 11th August 2018. A total of 101 specimens were collected that consists of 21 species from ten Families. The number of species various among plots of different trails. The number of species of the five plots that located around Trail No. 6, 7, 8 and 9 range between seven and ten species. On the other hand, each of the six plots that located around Trail No. 1, 2, 3, and 11 has no more than 2 species, with exception of Plot 7 at Trail No. 11 with 10 species. The plots with low number of species are also have relatively low land snail abundance and missing of many micro-snail species (< 5mm) as compare to the plot with high number of species. Overall, the species assemblage and diversity are similar to the previous sampling done in other non-limestone forest reserves in the east coast of Sabah.